THEOREMS ON THE NUMBER OF ROOTS OF A CUBIC EQUATION AND THEIR LOCATION AS A MEANS OF DEVELOPING STUDENTS' VISUAL THINKING - Шойра Абдієва; Ріскелді Тургунбаєв (Фізико-математична освіта)
Formulation of the problem. The basis of teaching mathematics is logical thinking, (which is associated with) based on the work of the left hemisphere. In scientific and methodological research, the volume of work related to the issue of organizing learning by coordinating the work of both the left and right hemispheres is increasing, that is, the development of other types of thinking, especially visual, along with logical thinking. Proposals have been developed on the methodology for the development of visual thinking of students in mathematics lessons. However, when studying the basics of algebra and analysis, improving the methodology for developing visual thinking and developing teaching materials for extracurricular activities are also urgent tasks.